Immunoregulatory factors (IRF3 and IRF7) serum levels and its relation to disease activity in Vitiligo patients - Anani, Maha; Hassan, Omayma; Attia , Fadia; Eyada , Moustafa; Mohammed, Ghada (Journal of Pakistan Association of Dermatologists, 2023)
Background Occurrence of vitiligo was reported in patients treated with IFN (Interferons) for melanoma, hepatitis C, and hepatitis B. This suggests IFN and its immunoregulatory factors may play a role in the pathogenesis of vitiligo. However, the immunopathogenesis remains largely unknown. Objective Explore the role of immunoregulatory factor 7 (IRF7) and immune-regulatory factor 3 (IRF3) in the serum of vitiligo patients. Methods We studied (n=94) vitiligo patients and compared them with healthy control subjects. All included subjects were submitted to full history taking, dermatological examination, VASI score calculation. IRF7 and IRF3 levels were assessed by IRF7 and IRF3 Immunoassay ELISA kit. Results Serum IRF-7 and IRF-3 are not elevated in vitiligo patients, and is associated with the least severity of the disease. Conclusion Our data suggest that the serum levels of type 1 IFN (IRF7) and (IRF3) are not implicated in vitiligo pathogenesis. However, Age and duration of disease showed a negative correlation with IRF3 serum levels with statistically significant correlation.